2018
DOI: 10.3389/fimmu.2018.01533
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-Coding RNAs Play a Role in the Pathogenesis of Psoriatic Arthritis by Regulating MicroRNAs and Genes Involved in Inflammation and Metabolic Syndrome

Abstract: Psoriatic arthritis (PsA) is an inflammatory arthritis, characterized by inflammation of entheses and synovium, leading to joint erosions and new bone formation. It affects 10–30% of patients with psoriasis, and has an estimated prevalence of approximately 1%. PsA is considered to be primarily an autoimmune disease, driven by autoreactive T cells directed against autoantigens present in the skin and in the joints. However, an autoinflammatory origin has recently been proposed. Long noncoding RNAs (lncRNAs) are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 45 publications
(56 reference statements)
0
17
0
Order By: Relevance
“…However, the potential mechanism is still not completely understood. Considering that lncRNAs-miRs-genes interactions have been established in the course of Psoriatic arthritis which is a chronic inflammatory arthritis [25], we expected that Mirt2 might modulate the inflammatory reaction via miR-377.…”
Section: Discussionmentioning
confidence: 99%
“…However, the potential mechanism is still not completely understood. Considering that lncRNAs-miRs-genes interactions have been established in the course of Psoriatic arthritis which is a chronic inflammatory arthritis [25], we expected that Mirt2 might modulate the inflammatory reaction via miR-377.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover we have evaluated epigenetic aspects that may be involved in the pathogenesis of the disease. Indeed we have applied this procedure in the study of other immune-mediated diseases and have identified non coding RNAs, in particular, long non coding RNAs (LncRNAs) as one of the epigenetic mechanisms able to modulate gene expression both directly and indirectly through microRNAs [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Long non‐coding RNAs are important and play diverse roles in regulating genetic transcription, modulating embryonic and neoplastic differentiation, pathogenesis of multiple diseases and drug resistance in tumour cells . LncRNA by itself cannot regulate these biological processes.…”
Section: Introductionmentioning
confidence: 99%